PENGARUH FIRM SIZE, CURRENT RATIO, PROFITABILITAS, DAN HUTANG HARGA SAHAM DENGAN DEVIDEN SEBAGAI MODERATING VARIABEL - Khasanah, Siti Khuswatun (Universitas Bunda Mulia, 2019)
The purpose of this study is to get a picture of the DPR moderating both partially and simultant on the Effect of DER, ROA, Firm Size on PER. The research approach used is a quantitative research approach. This type of research is documentation research while the nature of research is quantitative correlative. The target population of the study is the Manufacture Sector Sub Sector Consumer Goods Company in the Indonesia Stock Exchange, which amounted to 38 (thirty eight) issuers. While the sampling collection technique is a non-probability-purposive sampling so that the number of sample research targets is four issuers. The data analysis techniques applied include: 1. Descriptive Statistic Analysis; 2. Partial Regression Analysis; 3. Multiple Regression Analysis; and 4. Moderate Regression Analysis Model. the results of hypothesis testing through the t test, show that partially. DPR is able to moderate the influence of DER, ROA, Firm Size on PER. Whereas from the F test shows that simultant, the DPR is able to moderate the Effect of DER, ROA and Firm Size on PER. In this case, DER is a dominant and significant dominant predictor of PER. Keyword: Dividend Payout Ratio, Price Earning Ratio.